Analisis Pengaruh Kemudahan, Kenyamanan Bertransaksi, dan Keamanan Data terhadap Kepercayaan Nasabah pada Nasabah Generasi Z di UIN Sultan Thaha Saifuddin Jambi dalam Menggunakan BSI Mobile - Dani Setiarama; Rafidah Rafidah (Lembaga Yasin AlSys, 2025)
The increasing penetration of mobile banking services among younger generations faces challenges related to gaps in understanding the factors that influence user trust within local contexts. This study aims to analyze the influence of ease of use, transaction convenience, and data security on the trust of Generation Z customers in using BSI Mobile within the UIN Sultan Thaha Saifuddin Jambi environment. A quantitative approach was employed, with questionnaires distributed to 88 students from the 2022 cohort of the Faculty of Islamic Economics and Business. The research instrument used a Likert scale, and data were analyzed using F-test and t-test. The F-test results indicate that the three variables simultaneously have a significant effect on user trust (Fₕᵢₜᵤₙg = 34.204; significance = 0.000 < 0.05). Partially, the t-test shows that ease of use (tₕᵢₜᵤₙg = 2.436), transaction convenience (tₕᵢₜᵤₙg = 6.832), and data security (tₕᵢₜᵤₙg = 5.048) each have a significant effect on trust, as all values exceed the critical t value (1.6624) and are at a significance level below 0.05. These findings affirm that usability, transactional comfort, and data protection are significant determinants in building customer trust in mobile banking services, particularly among Generation Z university students.